Thrips (Insecta: Thysanoptera) in Andean crops in Puno, Peru - Bravo Portocarrero, Rosario Ysabel; Bezerra Lima, Elison Fabricio; Campos Quispe, Elva (Revista Colombiana de Entomología, 2026)
Thrips found in crops in the Puno highlands are occasional pests that damage foliage or flowers, and are  known to increase in population during periods of drought. To implementappropriate control strategies, it is necessary to correctly identify the species, commonly known by agricultural producers by the Aymara and Quechua terms “llaja” and “yana-usa,” which aretranslated as “black louse.” The study was conducted using specimens of potato (Solanum spp.), quinoa (Chenopodium quinoa), broad bean (Vicia faba), onion (Allium cepa), and alfalfa (Medicago sativa) in the towns of Illpa, Camacani, Ichu, and Mañazo. The species identified were: in potatoes, Frankliniella sp., Aff. simplex, F. occidentalis, F. australis, F. tuberosi, Thrips tabaci (Thripidae), and Haplothrips trellesi (Phlaeothripidae); in quinoa, F. sp. aff. simplex, F. occidentalis, F. tuberosi, T. tabaci; in broad beans, F. australis; in onions, T. tabaci and F. australis; and in alfalfa, F. australis, F. occidentalis, and T. tabaci. Historically, F. tuberosi has been considered the most widely distributed species in Andean crops; however, in the present study, it was only reported in potatoes and quinoa in a single location and with low population density. This study emphasizes the importance of ongoing sampling, identifying samples, and maintaining a repository of material for verification. In addition, H. trellesi is reported for the first time in the province of Puno.